Evaluation of Salt, Trace Mineral Sources, and Growth Implants on Performance of Stocker Cattle Grazing Native Flint Hills Pasture - C. S. Weibert; T. J. Spore; M. A. Johnson; F. K. Brazle; G. L. Kuhl; W. R. Hollenbeck; R. N. Wahl; Dale Blasi (Kansas Agricultural Experiment Station Research Reports, 2018)
Objective:Determine the efficacy of providing salt alone or with injectable trace minerals compared to a complete mineral supplement and growth implants for improving the growth of stocker calves grazing native grass pastures in the Flint Hills region of Kansas. Study Description:A total of 248 steers originating from Texas and New Mexico were used to determine the effects on performance when provided with salt blocks with or without an injectable trace mineral, compared to performance when provided with a complete mineral supplement. Moreover, the response of two commonly-used growth implants were evaluated. The Bottom Line:While there was no growth response to salt block and injectable trace mineral supplementation when compared to a complete mineral supplementation, there was a significant growth response with growth implants.
Keywords: salt; mineral; implants; stocker